Physico-chemical and microscopic quality of 14 trademark roasted and ground coffee - Teixeira, Olívia Reis; Passos, Flávia Regina; Mendes, Fabrícia Queiroz (Coffee Science - ISSN 1984-3909, 2016)
Coffee consumption is a global habit, this being one of the most consumed beverage in the world. Aimed to evaluate the physic-chemical quality and microscopic of roasted and ground coffee for the Brazilian market. Ash analysis, pH and titratable acidity in 14 marks roasted and ground coffee and its infusions were performed, and microscopy roasted and milled powder. Chemical analyzes of ash, pH and titratable acidity were no significant differences between treatments for both ground and roasted coffee infusions. The sample of Gourmet coffee powder showed lower ash content, higher acidity and lower pH. In microscopy, it was noted the presence of foreign materials in all samples, ranging in intensity from one brand to another. Gourmet coffee introduced himself as best quality. Four Traditional coffee brands had high ash content and impurities, suggesting intentional addition of foreign compounds.